A NorthStar IR sensor based localization system for mobile indoor robots - Ee, Hanyong (2011)
Localization systems are widely used in the world today to keep track of the location of many different objects. From our own location to the location of various objects, from a position on a map to the relative position in a building, many different systems can be used to detect and display the information on a screen.